Applying Snowball Throwing Technique in Improving Students’ Reading Comprehension at SMP Negeri 2 Tompaso - Tini Mogea (Student Scientific Creativity Journal, 2023)
The purpose of this research is to improve students’ reading comprehension through snowball throwing techniques at SMP Negeri 2 Tompaso. The students in the sample were all in first grade, and there were 22 of them. This is a quantitative study that used a pre-experimental design with one group pre-testing and post-testing. The instrument used in collecting data is a multiple-choice test. The result shows that the mean score of the students’ pretest was 6.9 and the mean score of the posttest was 7.9. Thus, it can be concluded that the application of the softball throwing technique improved students’ reading comprehension.